2009
DOI: 10.1111/j.1365-2230.2008.03190.x
|View full text |Cite
|
Sign up to set email alerts
|

Pemphigus foliaceus with prominent neutrophilic pustules initially presenting as erythroderma

Abstract: We report a 64-year-old man who presented with generalized erythroderma and erosions. The erythroderma improved generally as a result of systemic prednisolone treatment. After treatment, however, the patient developed annular erythema with tiny pustules. Histopathology, ELISA and immunoblot analysis showed the disease to be pemphigus foliaceus (PF) with prominent neutrophilic pustules. To our knowledge, this is the first known case of PF with prominent neutrophilic pustules presenting as erythroderma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 8 publications
2
8
1
2
Order By: Relevance
“…In 2004, Gabbi et al reported the case of a woman in her fifth decade of life, similar to our case with recurrent manifestations but less skin involvement. The most recent report was issued by Miyakura et al, presenting a case of a man who complained of erythrodermia, and similar progression of clinical manifestations to our case. All cases (including ours) exhibited a greater percentage of skin involvement when compared with other variants of PF; but a different age of presentation was observed in our case.…”
Section: Discussionsupporting
confidence: 82%
“…In 2004, Gabbi et al reported the case of a woman in her fifth decade of life, similar to our case with recurrent manifestations but less skin involvement. The most recent report was issued by Miyakura et al, presenting a case of a man who complained of erythrodermia, and similar progression of clinical manifestations to our case. All cases (including ours) exhibited a greater percentage of skin involvement when compared with other variants of PF; but a different age of presentation was observed in our case.…”
Section: Discussionsupporting
confidence: 82%
“…Unlike patients with pemphigus vulgaris (PV), patients with PF rarely develop mucosal lesions. The erosions may become generalized, and occasionally an exfoliative erythroderma may develop 5–10 . PF presenting as an exfoliative erythroderma has been reported more frequently in the endemic form of PF, fogo selvagem , 1 although a case reported by Nousari et al 6 describes a patient with non‐endemic erythrodermic PF, ultimately proving to be fatal.…”
Section: Discussionmentioning
confidence: 99%
“…Although rarely PF could be associated with GPP; interestingly we found case reports that PF has initially manifested as neutrophilic pustules but in those cases, pathologic changes and DIF studies of the pustules confirmed PF not GPP [1,5,6]. In our patient pustular lesions had no pathologic criteria of PF and were preceded by annular erythema, so she was not a case of pustular PF.…”
Section: Discussionmentioning
confidence: 75%
“…Pemphigus foliaceus (PF) is an autoimmune bullous disease (AIBD) which is presented by superficial flaccid blisters, erosions, scales and crusts on the seborrheic areas of the face and trunk without mucosal involvement [1]. Pathologically, PF is characterized by granular layer acantholysis with acantholytic cells and intraepidermal deposition of Immunoglobulin G (IgG) and complement component 3 (C3) on immunofluorescent studies as a result of antibody production against desmoglein 1, a component of desmosome [2].…”
Section: Introductionmentioning
confidence: 99%